The Analysis Of Students’ Critical Thinking In Writing Hortatory Exposition Text - Sulton Dedi Wijaya; Intan Suhardi Yanti; Armeria Wijaya (Universitas Muhammadiyah Surabaya, 2019)
This study which entitles the analysis of students’ critical thinking in writing hortatory exposition text focuses on elaborating the critical thinking of the second social graders students in SMAN 1 Tarik. This study also aims to find out the factors influencing the students’ critical thinking. This study employs descriptive qualitative as the research design. The data which is used to be analyzed is from the students’ writing hortatory exposition text. The result of this study showed that 43% of students are categorized to the developing level. While 33% students are categorized to beginning level and 23% students are in unacceptable level. The limited critical thinking standard showed in the students’ writing such as clarity, relevancy, and logic. The factors of critical thinking also can be found in this study. The interview results show that the students which have better level of critical thinking, they have reading habit and update the recent information. Other finding of this study is external closures can influence the critical thinking but in this case, the researcher didn’t find any students which participate in any seminars or public discourse which can develop the way of students thinking. In short, having much knowledge about recent issue helps the students to be more critical. Therefore students need to develop their critical thinking through some factors that influence the critical thinking. Key words: Argument, Critical thinking, Hortatory exposition text, Writing